PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 18 PEKANBARU - Astuti, Indriani; Alim, Jesi Alexander; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on 12-27 March 2015. The data shown the either learning process increased. The basic score of daily examination as 16,71% which 22 students passed and 9 students failed. The ending of daily examination was 70,97% and the average was 81,13% on the passing grade. The second daily examination also increased from basic score as 23,10% which 29 students passed and 3 students failed. The ending of second daily examination was 90,63% and the average was 85,97. Based on the explanation above it can be concluded that the implementation of direct learning increased students’ achievement the result of science studies of students III grade of State Elementary School 183 Pekanbaru.Keywords : Direct Learning, Students Achievement The Result Of Science Studies